ECC condensation research in T-junction. (September 2016) - Ren, W.Y.; Fu, X.L.; Tian, W.X.; Dong, Bo; Bian, J.W.; Yu, G.J.; Yang, Y.H.; Qiu, S.Z.; Su, G.H.
Highlights: ECC condensation research based on China PWR- CPR1000. The correlation of condensation based on XJTU-ECC test was proposed. Wide range of RT number from 0 to 3.5 were analyzed within condensation. A new analysis method was proposed by using the mass fraction and RT number. The test report a conservative results on ECC component than RELAP5 calculation.